Pendugaan Potensi Simpanan Karbon Pada Tegakan Acacia Mangium Di Hutan Penelitian BKPH Parung Panjang, KPH Bogor - Setiajiati, Fitta; Faridah, Dedeh; Pratama, Moh Rizal; Amelia Febriyanti, Censa; Ramdhan, Taufik; Bahruni (JURNAL AGRIMENT, 2023)
Climate change is a critical issue currently and is often linked to forest resources as a source of carbon storage. In response, we need to study the potential for carbon stock in forest ecosystems in an effort to mitigate climate change. This research was conducted in acacia stands in the BKPH Parung Panjang research forest, KPH Bogor, and aimed to estimate the potential of carbon stock in plantations of the acacia forest. Apart from being a forest with particular research purposes, acacia stands can store carbon of 36.32 tons/ha or 799.04 tons of CO2 eq on a total area of 6 ha. This carbon stock value is much smaller than that of acacia stands in general because the tree diameter is still relatively small. Even though this acacia plantation forest does not contribute significantly to climate change mitigation, it contributes positively to creating coolness for the surrounding community.